Autopsy translates in Arabic to al-tashreeh. Could this term influence its acceptability?. (January 2015) - Al-Amad, Suhail H.; Cordner, Stephen; Al Haddidi, Mu'men; Al-Amad, Hani
Abstract: It is not unusual for laypersons to object on the conduct of an autopsy of a loved one for fear of disfigurement or burial delays. In this paper, we discuss a new possible reason for objection among Arabic speaking communities related to the language. The Arabic word for autopsy is "al-tashreeh" which, when examining its other linguistic uses, might result in wrong inferences among laypersons.